Analisis Karakteristik Penggunaan Moda Akses Bandara Internasional Yogyakarta - El Hafizah, Nafilah; Hidayat, Erwin (Jurusan Teknik Sipil, 2019)
The new Yogyakarta International Airport began operations with an airport area of 645.63 hectares with a capacity of 14 million passengers a year. Access to the Yogyakarta international airport is distributed to 4 routes to the airport at Wates national road, Karangnongko road, the Southern Cross Road, Daendels road which is using the railroad mode. This study uses revealed preference analysis which is the approach by conveying a fact choice statement to be given an assessment by the respondent. The sample collection is assumed by the peak passenger of the Adisucipto airport, because the Yogyakarta International Airport is recently opened. It is expected to be able to represent demand predictions at the Yogyakarta International airport in the future. The results of the questionnaire were then processed by using statistical analysis to determine the factors that influence the selection of transportation modes to and from the airport. In research, the factors that influence mode choice are travel costs, travel time, travel distance, and generalized costs. The results illustrate that prospective air transport users are more dominant in choosing travel cost attributes compared to other attributes that influence. With the coefficient of determination is 0.528 and the results of data analysis for the selection of mode of transportation using private vehicles is 57% and public transportation is 43%..